2017
DOI: 10.1155/2017/5140506
|View full text |Cite
|
Sign up to set email alerts
|

In VitroScreening of Three Indian Medicinal Plants for Their Phytochemicals, Anticholinesterase, Antiglucosidase, Antioxidant, and Neuroprotective Effects

Abstract: Cooccurrence of Diabetes Mellitus and Alzheimer's disease in elder people prompts scientists to develop multitarget agents that combat causes and symptoms of both diseases simultaneously. In line with this modern paradigm and as a follow-up to our previous studies, the present study is designed to investigate the crude methanolic extracts and subsequent CHCl3, n-BuOH, and H2O fractions of Acalypha alnifolia, Pavetta indica, and Ochna obtusata for their inhibitory activities towards specific targets involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Fractions 1‐25 were eluted with chloroform: methanol (95:5), fractions 28‐40 were eluted with chloroform: methanol (90:10), fractions 42‐85 were eluted with chloroform: methanol (80:20), fractions 90‐135 were eluted with chloroform: methanol (75:25), and fractions 140‐165 were eluted with chloroform: methanol (50:50). All the fractions were screened for the presence of various active phytocompounds . All the collected fractions (F 1 ‐F 5 ) were evaluated for in vitro anti‐arthritic activity by inhibition of protein denaturation method (protocol not shown here).…”
Section: Methodsmentioning
confidence: 99%
“…Fractions 1‐25 were eluted with chloroform: methanol (95:5), fractions 28‐40 were eluted with chloroform: methanol (90:10), fractions 42‐85 were eluted with chloroform: methanol (80:20), fractions 90‐135 were eluted with chloroform: methanol (75:25), and fractions 140‐165 were eluted with chloroform: methanol (50:50). All the fractions were screened for the presence of various active phytocompounds . All the collected fractions (F 1 ‐F 5 ) were evaluated for in vitro anti‐arthritic activity by inhibition of protein denaturation method (protocol not shown here).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, AChE and BuChE have been found to be responsible for upregulating the expression of the amyloid precursor protein (APP). Thereby dual inhibition of AChE and BuChE could be effective in the management of AD symptoms as it would result in the increase of ACh synaptic levels and the decrease of neurotoxic Aβ fibrils [28,29].Commercially available synthetic drugs used for management of AD have been associated with drawbacks like gastrointestinal disturbances, moderate effectiveness, high cost and short half-life [30]. Natural product-based compounds have been increasingly explored for better effects.…”
Section: Bioactivity Of Gold Nanoparticlesmentioning
confidence: 99%
“…[37], Polygonum hydropiper [38], and Alpinia zerumbet [39]. Moreover, DK induces the production of the proangiogenic tumor-derived protein Vascular endothelial growth factor (VEGF) in colorectal cancer cells [37]; exerts anticholinesterase, antioxidant, and neuroprotective effects [40]; and promotes the differentiation of MC3T3-E1 osteoblasts [39]. In this study, the results of MTT, wound-healing, and invasion assays revealed that DK significantly decreased the migration and invasion of MDA-MB-231 cells (Figure 8A–C).…”
Section: Discussionmentioning
confidence: 99%